Pengaruh Job Involvement terhadap Komitmen Organisasi pada Volunteer di Yayasan Pemuda Peduli - Nurul Shafira; Lisa Widawati (Bandung Conference Series: Psychology Science, 2023)
Organizational commitment reflects the level of seriousness of members in carrying out their duties and functions. Many researchers use organizational commitment as the main focus of their research. The more variables associated with organizational commitment. One of them is job involvement. There have been quite a number of studies examining the effect of job involvement on organizational commitment. However, most of the research is only in the profit sector. Meanwhile, very little has been done in the public sector, and there has been no research examining the level of influence of job involvement on organizational commitment in the non-profit sector, especially among volunteers. The Youth Cares Foundation is a non-profit organization with quite a number of volunteers who have been involved in it for a long time. This study aims to determine and analyze the level of influence of Job involvement on Organizational Commitment to Volunteers at Yayasan Pemuda Peduli. The research method used is the causality method with a total of 41 volunteers at the Youth Care Foundation. This study uses job involvement measurement tools from Kanungo's theory, namely the Job involvement Questionnaire (JIQ) and the Organizational Commitment Questionnaire (OCQ) which emerged together with the organizational commitment theory from Mowday, Porter & Steers. Based on the results of a simple linear regression analysis test with a significance level = 0.05, R^2 = 0.717 was obtained, indicating that there was a significant positive effect of job involvement on organizational commitment to volunteers at Yayasan Pemuda Peduli by 71.7%. Komitmen organisasi mencerminkan tingkat kesungguhan anggota dalam menjalankan tugas dan fungsinya. Banyak peneliti yang menggunakan komitmen organisasi menjadi fokus utama penelitiannya. Semakin banyak pula variabel-variabel yang dikaitkan dengan komitmen organisasi. Salah satunya job involvement, sudah cukup banyak penelitian yang meneliti terkait pengaruh job involvement terhadap komitmen organisasi. Namun penelitian tersebut kebanyakan hanya di sektor profit. Sedangkan sangat sedikit yang dilakukan disektor publik, dan belum ada penelitian yang menguji tingkat pengaruh job involvement terhadap komitmen organisasi pada sektor non profit, khususnya pada kalangan volunteer. Yayasan Pemuda Peduli merupakan organisasi non profit dengan cukup banyak volunteer yang cukup lama tergabung didalamnya. Penelitian ini bertujuan untuk mengetahui dan menganalisis tingkat pengaruh Job involvement terhadap Komitmen Organisasi pada Volunteer di Yayasan Pemuda Peduli. Metode penelitian yang digunakan adalah metode kausalitas dengan jumlah subjek 41 volunteer di Yayasan Pemuda Peduli. Penelitian ini menggunakan alat ukur job involvement dari teori Kanungo yaitu Job involvement Questionnaire (JIQ) dan Organizational Commitment Questionaire (OCQ) yang muncul bersama teori komitmen organisasi dari Mowday, Porter & Steers. Berdasarkan hasil uji analisis regresi linear sederhana dengan taraf signifikansi = 0.05 diperoleh = 0,717 yang menandakan terdapat pengaruh signifikan positif job involvement terhadap komitmen organisasi pada volunteer di Yayasan Pemuda Peduli sebesar 71.7%.